Nano-TiO2 Doped Chitosan Scaffold for the Bone Tissue Engineering Applications - Pawan Kumar (International Journal of Biomaterials)
The present focus is on the synthesis of highly effective, porous, biocompatible, and inert scaffold by using ceramic nanoparticles and natural polymer for the application in tissue engineering. Freeze-drying method was used to fabricate nano-TiO2 doped chitosan sample scaffold. Nano-TiO2/chitosan scaffold can considered as an effective solution for damaged tissue regeneration. The interaction between chitosan (polysaccharide) and nano-TiO2 makes it highly porous and brittle that could be an effective substitute for bone tissue engineering. The TiO2 nanoparticles have a great surface area and inert properties while chitosan is highly biocompatible and antibacterial. The physiochemical properties of TiO2 nanoparticles and scaffold are evaluated by XRD and FTIR. The nanoparticles doped scaffold has given improved density (1.2870g/cm3) that is comparatively relevant to the dry bone (0.8 - 1.2 gm/cm3). The open and closed porosity of sample scaffold were measured by using Brunauer–Emmett–Teller analyzer (BET) and scanning electron microscopy (SEM). The mechanical properties are examined by stable microsystem (Texture Analyzer). The in vitro degradation of scaffold is calculated in PBS containing lysozyme at pH 7.4. Electron and fluorescence microscopy are used to study morphological characteristics of the scaffolds and TiO2 nanoparticles. The growth factor and drug-loaded composites can improve osteogenesis and vascularization.